Spore dissemination and germination - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
You are reading the first issue of SPORE, the bulletin of the Centre for Agricultural and Rural Technology. Yet another bulletin in a world where every institution from the tiniest to the mightiest has its own newsletter. But SPORE is different. Its...